P094 CPAP Service Patient Experience Survey. (7th October 2021) - Mihai, R; Ellis, K; Verginis, N; Davey, M; Nixon, G
Abstract: Introduction: Increasing numbers of children with obstructive sleep apnoea require continuous positive airway pressure (CPAP) treatment. We aimed to collect feedback from parents/carers about our CPAP education and follow-up programme. Methods: An online survey link was texted to families of children starting outpatient CPAP from Jan 2019 -Feb 2021. Questions assessed satisfaction with the CPAP initiation process, including education by our nurse educator (NE), mask fitting, using equipment, accessing help, confidence using CPAP and follow up. Open-ended feedback was invited. Results: 17/55 (31%) of eligible families responded. "Very satisfied" responses regarding CPAP education ranged from 76% (discussion of costs) to 94% (machine use and maintenance). All families felt confident starting CPAP at home. Two reported issues starting CPAP, but reported feeling fully supported by staff remotely to troubleshoot. All families were "somewhat" or "very satisfied" with NE follow-up, with 2 families more neutral about physician follow-up. Two families reported lower satisfaction ("somewhat dissatisfied" or neutral) with the range of paediatric masks, rather than with the mask fitting process itself. Of 14 general comments, 64% were positive (most common theme was high standard of care from the NE); 21% negative (lack of mask choices, location of consulting suites); and 15% neutral. Suggestions for improvement included financial support information, support groups and online consumable ordering. Discussion: Families feel confident and well supported to commence outpatient CPAP, highlighting the care, knowledge and support provided by our team. Findings emphasize the importance of a dedicated NE. Suggestions provided will inform future service improvements.